Spatial and temporal heterogeneity of macrofungi in the protected forests of Southern India - Pavithra, M.; Sridhar, K. R.; Greeshma, A. A.; Karun, N. C. (International Journal of Agricultural Technology, 2016)
Macrofungal inventory at fortnightly intervals up to 10 weeks in two protected forests (arboretum and botanical garden) of the Southwestern India during southwest monsoon yielded 53 species belong to 33 genera. A total of 29 (22 genera) and 36 (26 genera) species were recovered in arboretum and botanical garden, respectively. Sporocarp richness was higher in botanical garden than in arboretum (742 vs. 684). Richness of species, genera, sporocarps and diversity attained the highest during 4th wk except for sporocarps in arboretum (2nd wk). The overall Sørensen’ssimilarity was 36.9% between habitats, while between fortnights of habitats ranged from 18.2% (8th wk) to 34.8% (2nd wk). Both habitats were dominated by four species without overlap. The highest number of fungi was obtained on soil in botanical garden (29.3%), woody debris in arboretum (18.5%) and four species occurred on two substrates. Species richness was higher in medium and coarse than in fine woody debris. Among the abiotic factors, depth of leaf litter, soil moisture, soil pH and total phosphorus content of soil were significantly differed between habitats (P < 0.05). In arboretum, species richness vs. soil conductivity showed a positive correlation (R = 0.745), while species richness vs. soil phosphorus content was negatively correlated (R = - 0.747). Nearly 43% of macrofungi in this survey have economic value as edible (12 spp.), medicinal (7 spp.) and mycorrhizal (10 spp.). Up to 7 species have duel benefit as edible/medicinal (1 sp.), edible/mycorrhizal (4 spp.) and medicinal/mycorrhizal (2 spp.). Results of this study advocate future prospects of forest management in the Southwestern India in favor of production of macrofungi during southwest monsoon.